An examination of participation in sneaker culture: consumer motivations and responses to co-branding between luxury apparel and athletic shoe brands - Louis Vuitton and Nike - Shin, Donghoon, author; Hyllegard, Karen, advisor; Ogle, Jennifer, committee member; Chai, DaeSeok, committee member (Colorado State University. Libraries, 2023)
This thesis investigated the phenomenon of 'sneaker culture' influence on the contemporary fashion market by examining consumer perspectives and their motivations for engaging in this subculture and by exploring their responses to the collaborative marketing strategy called co-branding. This research examined the co-branding of luxury apparel brands and athletic shoe/sportswear brands through the collaboration between Louis Vuitton and Nike. This research was guided by the lens of fandom and participatory culture, and it employed an inductive approach to draw general conclusions from specific observations (i.e., interviews). This study was conducted by interviewing 'sneakerheads' who were expected to be particularly interested in this collaboration between luxury and athletic brands. Through a qualitative research method, this study provides insight into consumers' (i.e., sneakerheads) perceptions of the value of this type of co-branding. Findings also provide insights for fashion companies to understand the specific motivations of consumers who participate in sneaker culture and their behavior/response (i.e., consumer attitudes and purchase intentions) to co-branding between luxury brands and athletic shoe/sportswear brands.
Keywords: sneakerheads; co-branding